Validation of associations, alliances and orders of the Algerian forest and scrub vegetation - Meddour, Rachid; Mucina, Ladislav (Mediterranean Botany, 2021)
This paper presents description protocols of 13 new associations, 12 alliances, and 1 order of the Algerian forest and forest-associated vegetation of the classes Quercetea ilicis, Junipero-Pinetea sylvestris, Quercetea pubescentis, Alno glutinosae-Populetea albae, Alnetea glutinosae, Franguletea and Nerio-Tamaricetea.